Diagnostic Confidence of Contrast-Enhanced T1-Weighted MRI for the Detection of Brain Metastases: 3D FSE versus 3D GRE–Based Sequences - Gule-Monroe, Maria; Chasen, Nathan; Long, James P.; Kumar, Vinodh A.; Shah, Komal; Chen, Melissa; Stafford, Jason; Chung, Caroline; Wintermark, Max; Hou, Ping; Sura, Ekta; Wang, Chenyang; et al. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: This retrospective study evaluated the utility of contrast-enhanced T1-weighted 3D fast spin-echo–based sampling perfection with application-optimized contrasts by using different flip angle evolutions (SPACE) sequences for brain metastasis detection on 3T MRI compared with a gradient-recalled echo–based 3D FLASH sequence.MATERIALS AND METHODS: We identified all patients at a single institution who underwent SPACE and 3D FLASH sequences as part of a practice quality-improvement project. Their medical records were retrospectively reviewed. Five certified neuroradiologists reviewed the images, with at least 2 weeks’ separation between scoring sequences for the same patient. We evaluated the following parameters: number of metastatic lesions, number of indeterminate lesions, lesion margin, contrast-to-noise ratio (CNR), extent of image artifacts, and overall image quality. The CNR was also quantified for solidly enhancing lesions of >1 cm.RESULTS: We identified 220 patients who underwent SPACE and 3D FLASH sequences (the order of the sequences was equally distributed). Of these, 79 had brain metastases on imaging, and 7 were excluded; thus, 72 patients were included in the study. Twenty patients were scored by 2 radiologists. Of the 92 evaluations, SPACE detected more lesions than 3D FLASH in 35, while 3D FLASH detected more lesions in 10. More indeterminate lesions were seen on 3D FLASH (n = 27) than on SPACE (n = 9). For the lesion margin, CNR, and overall image quality on a Likert scale, SPACE performed significantly better than 3D FLASH, with fewer image artifacts (P < .00001). Higher quantitative CNRs were found on SPACE than on 3D FLASH images, though this result was not statistically significant (median = 22.9 versus 15.5, respectively, P = .134). There was a high interreader lesion detection concordance with the Krippendorf α ordinals at 0.962 for SPACE, 0.870 for 3D FLASH, and 0.918 for the 2 sequences combined.CONCLUSIONS: Compared with 3D FLASH, the SPACE sequence detected more metastatic lesions and was rated higher for image quality, lesion margin, and CNR, with fewer artifacts. Importantly, the SPACE sequence resulted in increased reader confidence, with fewer indeterminate lesions detected.CEcontrast-enhancedCNRcontrast-to-noise ratioGRAPPAgeneralized autocalibrating partially parallel acquisitionIRinversion recoverySEspin-echoSPACEsampling perfection with application-optimized contrasts by using different flip angle evolutionVIBEvolumetric interpolated breath-hold examination